A vaccine combining two Leishmania braziliensis proteins offers heterologous protection against Leishmania infantum infection. (August 2016) - Duarte, Mariana C.; Lage, Daniela P.; Martins, Vívian T.; Costa, Lourena E.; Lage, Letícia M.R.; Carvalho, Ana Maria R.S.; Ludolf, Fernanda; Santos, Thaís T.O.; Roatt, Bruno M.; Menezes-Souza, Daniel; Fernandes, Ana Paula; Tavares, Carlos A.P.; et al.
Graphical abstract: Highlights: Two antigenic L. braziliensis proteins were selected. They present high amino acid sequence homology between different Leishmania species. A polyproteins vaccine was developed based on these two recombinant proteins. BALB/c mice were immunized and challenged with L. infantum promastigotes. The protection was based on low parasite levels and a parasite-specific Th1 immunity. Abstract: In the present study, two Leishmania braziliensis proteins, one hypothetical and the eukaryotic initiation factor 5a (EiF5a), were cloned and used as a polyproteins vaccine for the heterologous protection of BALB/c mice against infantum infection. Animals were immunized with the antigens separately or in association, and in both cases saponin was used as an adjuvant. In the results, spleen cells from mice inoculated with the individual or polyproteins vaccine and lately challenged produced significantly higher levels of protein- and parasite-specific IFN-γ, IL-12, and GM-CSF, when both a capture ELISA and flow cytometry assays were performed. Evaluating the parasite load by a limiting dilution as well as by RT-PCR, these animals presented significant reductions in the parasite number in all evaluated organs, when compared to the control (saline and saponin) groups. The best protection was reached when the polyproteins vaccine was employed. Protection was associated with the IFN-γ production against parasite extracts, which was mediated by both CD4 + and CD8 + T cells and correlated with the antileishmanial nitrite production. In this context, this vaccine combining two L. braziliensis proteins was able to induce a heterologous protection against VL, and could be considered in future studies to be tested against other Leishmania species or in other mammalian hosts.